ANALISA PENERAPAN GOOD CORPORARTE GOVARNANCE DI PERBANKAN SYARIAH - Joko Hadi Purnomo (Al Hikmah: Jurnal Studi Keislaman, 2015)
Abstract: A good corporate governance (GCG) is a structure in whichstakeholders, shareholders, commissioners and managers make up thecompany's goals in addition to monitoring performance. The system ofgovernance in Islamic banks could bridgea wide range of efforts in addressingthe shared interest through the so-called Governance Committee. Thus, theimplementation of good corporate governance in Islamic banks rests on fivemain pillars namely transparency, responsibility, accountability, fairness, andindependency.Keywords: governance, responsibility, fairness